Type of Feeding and Age Group with the Incidence of Diarrhea in Infants Aged 0–6 Months - R Yusuf Firdaus Albana; Raden Ayu Libert Gatho Reza (Sarana Ilmu Indonesia (Salnesia), 2026)
Diarrhea remains a common health problem among infants, particularly during the first six months of life. Differences in feeding methods and the level of maturity of the infant digestive system are believed to influence susceptibility to diarrhea. This study aimed to determine the relationship between the incidence of diarrhea and type of feeding (exclusive breastfeeding or formula feeding) as well as infant age group (0–3 months and 4–6 months). Medical records of 84 infants treated at Hermina Hospital, Bogor, during 2025 were analyzed using the Chi-square statistical test, while the strength of the association was measured using prevalence ratio analysis. The results showed that infants who received formula feeding tended to experience diarrhea more frequently than those who received exclusive breastfeeding, and this difference was statistically significant. In addition, older infants tended to experience diarrhea more frequently than younger infants, and this difference was also statistically significant. These findings emphasize the importance of promoting exclusive breastfeeding as a preventive measure against diarrhea in infants, while also highlighting the need for close monitoring of early signs of digestive disorders, especially during the transitional phase after two months of age. Providing educational support for parents and healthcare workers is also important to improve understanding of the benefits of exclusive breastfeeding and to facilitate early detection of diarrhea.